2009 H1N1 Influenza - Seth J. Sullivan, MD; Robert M. Jacobson, MD; Walter R. Dowdle, PhD; and Gregory A. Poland (Medisur)
Within 2 months of its discovery last spring, a novel influenza A (H1N1) virus, currently referred to as 2009 H1N1, caused the first influenza pandemic in decades. The virus has caused disproportionate disease among young people with early reports of virulence similar to that of seasonal influenza. This clinical review provides an update encompassing the virology, epidemiology, clinical manifestations, diagnosis, treatment, and prevention of the 2009 H1N1 virus. Because information about this virus, its prevention,and treatment are rapidly evolving, readers are advised to seek additional information. We performed a literature search of PubMed using the following keywords: H1N1, influenza, vaccine, pregnancy, children, treatment, epidemiology, and review. Studies were selected for inclusion in this review on the basis of their relevance. Recent studies and articles were preferred.